Health and social care professionals’ experiences of collaborative planning—Applying the person‐centred practice framework - Jobe, Ingela (Nurs Open, 2020)
AIM: To explore how person‐centred practice framework can be applied to professionals participating in collaborative planning. DESIGN: An explorative, deductive approach. METHOD: Eleven professionals from health care and social care participated in the study. A deductive content analysis was performed using a framework for person‐centred practice for the analysis. RESULTS: Practicing person‐centred care and collaborative planning is a complex process that needs to take into account system factors on both the macro‐ and the microlevel. Everyone working within the system needs to apply the same approach. Using a framework analysis offered new insights into how person‐centred care is expressed in practice during collaborative planning between the patient, and healthcare and social care professionals.